Peningkatan Kapasitas Sosial Masyarakat Desa melalui Edukasi Lingkungan dan Penguatan Keterampilan Komunikasi di Desa Jimbaran Wetan, Wonoayu, Sidoarjo - Arianto, Bisma; Yanus, Yanus Sumitro; Yuli, Yuli Kurnia Firdausia; Nurdina, Nurdina; Onny, Widiar Onny Kurniawan (Ekobis Abdimas, 2026)
This community service program aims to strengthen the social skills of the community in Jimbaran Wetan Village, Wonoayu District, Sidoarjo Regency, through environmental education and communication skills development. This program is based on the belief that empowering village communities is crucial to maximizing their local potential in a productive, sustainable, and environmentally friendly manner. Jimbaran Wetan Village has strong potential in agriculture, handicrafts, and craft products, but still faces challenges in utilizing local resources, managing businesses, increasing environmental awareness, improving communication skills, and promoting their products. Therefore, this project aims to guide and support the community to identify their local potential, understand the principles of sustainable entrepreneurship, increase environmental awareness, and develop communication skills to market local products. The implementation of this activity includes coordination with partners, preparation of infrastructure and equipment, as well as educational activities, training, and support for three months, from April to June 2026. The target of this activity is the residents of Jimbaran Wetan Village. The expected results of this activity are increased understanding, increased awareness, and improved skills in the community regarding the utilization of local potential, based on environmental awareness, as well as increased community confidence in developing productive and sustainable businesses. seeds, proper watering and fertilisation as well as the placement of polybags that are in accordance with the growing conditions of the seed growing requirements.